2007
DOI: 10.1088/0004-6256/135/1/326
|View full text |Cite
|
Sign up to set email alerts
|

Deep Optical Imaging of Starbursting “Transition” Dwarf Galaxies

Abstract: A subgroup of dwarf galaxies have characteristics of a possible evolutionary transition between star-forming systems and dwarf ellipticals. These systems host significant starbursts in combination with smooth, elliptical outer envelopes, and small H i content; they are low on gas and unlikely to sustain high star-formation rates over significant cosmic time spans. We explore possible origins of such starburst "transition" dwarfs using moderately deep optical images. While galaxy-galaxy interactions could produ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 64 publications
4
36
0
Order By: Relevance
“…In this respect, BCDs are particularly Appendices are available in electronic form at http://www.aanda.org interesting as the burst durations are typically of a few 100 Myr (McQuinn et al 2010a), thus they must evolve into another type of dwarf as the starburst fades. The possibility of morphological transformations between low-mass galaxies is also suggested by the existence of "transition type" dwarfs, which have intermediate properties between Sphs and Irrs/BCDs (e.g., Sandage & Hoffman 1991;Mateo 1998;Dellenbusch et al 2007Dellenbusch et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, BCDs are particularly Appendices are available in electronic form at http://www.aanda.org interesting as the burst durations are typically of a few 100 Myr (McQuinn et al 2010a), thus they must evolve into another type of dwarf as the starburst fades. The possibility of morphological transformations between low-mass galaxies is also suggested by the existence of "transition type" dwarfs, which have intermediate properties between Sphs and Irrs/BCDs (e.g., Sandage & Hoffman 1991;Mateo 1998;Dellenbusch et al 2007Dellenbusch et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Davies & Phillipps 1988; Moore et al 1996; van Zee, Skillman & Haynes 2004; Sabatini et al 2005; Dellenbusch, Gallagher & Knezek 2007). Dellenbusch et al (2008) conclude that five galaxies in their study are members of the so‐called dwarf transition galaxy class, in between the dI and dE classifications. Dolphin et al (2005) conclude that several dE galaxies observed in their programme would have looked identical to dIs if they had been observed two billion years earlier.…”
Section: Introductionmentioning
confidence: 92%
“…It has been suggested that these young objects might be the predecessors of the predominantly early-type, gas-poor and low-metallicity population of dE and dSph dwarf galaxies (e.g. Dellenbusch et al 2008). The favourite theory to explain the gas depletion that such transition implies is again based on starburst driven superwinds (Larson 1974, Dekel & Silk 1986.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, observational studies indicate that in many cases, galactic starburst episodes are centrally concentrated (e.g. Marlowe et al 1995;Taniguchi, Trentham & Shioya 1998;Cairós et al 2003;Dellenbusch et al 2008); an effect that has been so far neglected in superwind analytical models.…”
Section: Introductionmentioning
confidence: 99%